Pengaruh Pengetahuan, Keterampilan, dan Sikap Kerja Terhadap Kepuasan Kerja Pegawai Kementerian Investasi RI/BKPM (Jurnal Simki Economic, 2024)
This study aims to determine the influence of knowledge, skills, and work attitudes on employee job satisfaction at the Ministry of Investment of the Republic of Indonesia / BKPM. This type of research uses quantitative methodology with a survey of 77 employees, this study applies Structural Equation Modeling (SEM) for data analysis. The results of the study are expected to provide insight into how aspects of knowledge, skills, and work attitudes contribute to job satisfaction, as well as their implications for human resource management in the government environment. This research is relevant for managerial practice, particularly in designing HR policies that increase job satisfaction and organizational efficiency. The study also offers a theoretical contribution by examining and expanding the literature on knowledge, skills, and work attitudes in the context of job satisfaction in the government sector.